Visualisasi Aljabar untuk Memecahkan Masalah Realistis Berplatform E-Learning Moodle - Siregar, Nurfadilah; Fitriawan, Dona; Hartoyo, Agung; Sulistyowati, Endar (Media Pendidikan Matematika, 2025)
The purpose of this study is so that second semester students who take linear algebra courses are able to analyze their visualization understanding in solving problems presented with real life. Specifically we want to know: 1) how they understand the problem; 2) how to visualize the problem; 3) how they get the conclusion from their visualization; 4) how it impacts the course itself on the moodle e-learning platform. The type of research used is qualitative with descriptive-explorative methods, namely exploring all things that exist in the implementation of learning, processing problems and their answer steps, visualizing algebra, e-learning platforms, and exploring the results of surveys and interviews of students.The subjects in this study were all students who took elementary linear algebra courses in classes A1, A2, and B totaling 81 students who were gathered in one lecture class together in Building B of Tanjungpura University. Data from written tests, surveys, questionnaires, and responses were then explored descriptively to get conclusions in accordance with the problem formulation. Based on the analysis of several scientific journals on mathematical visual thinking skills in solving mathematical problems, visualization can improve the development of thinking, mathematical understanding from non-concrete to concrete. According to several journal sources reviewed, there are several ways to solve problems by implementing mathematics learning programs that increase learners' understanding and responsiveness when solving problems including: open minds approach, meansends learning, collaborative learning, trade-a-problems learning, problem and project based learning, visual thinking learning, RME, CTL, and eliminatin aplikation learning.